Fixing global finance: unfinished business - Grenville, Stephen (2016)
The 2008 financial crisis was hugely damaging. The focus of reform has been on increasing banks‘ required capital. Together with the other measures taken, this makes a repetition of 2008 less likely. However, the crisis also taught us that financial markets do not work as well as we thought. Financial innovation has made the markets more volatile, short-term focused and more pro-cyclical. Not much has been done to address this issue. This paper suggests that the government-guaranteed banking sector should be separated much more clearly from the rest of the financial sector, which should be more explicitly identified as a risky sector. This separation would change the way the financial sector is managed (with conservative management returning to the banking sector). Such beneficial changes would reduce the size of the financial sector, which currently attracts too many of our best brains.